2022
DOI: 10.1002/lsm.23524
|View full text |Cite
|
Sign up to set email alerts
|

High energy, double pass helium plasma dermal resurfacing: A prospective, multicenter, single‐arm clinical study

Abstract: Background: A previous multi-center clinical study of low energy (20% power), single-pass helium plasma dermal resurfacing (HPDR) showed positive results but did not fully reveal the true potential of this novel technology. A second multi-center clinical study, reported herein, was therefore undertaken to evaluate efficacy and safety of high energy (40%), double pass HPDR for treatment of facial rhytids (ClinicalTrials.gov Identifier: NCT04185909). Methods: Fifty-five eligible subjects seeking improvement in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This study evaluated the effects of LICAP on photoaginginduced wrinkles in an animal model and the expression profiles of extracellular matrix proteins in human dermal fibroblasts. LICAP was defined to distinguish the device from other conventional CAP devices that are designed to be used in a destructive manner, such as for skin resurfacing, [14][15][16] cancer therapy, 17 or tissue coagulation. 18 In this paper, the term LICAP indicates a physical plasma device that is designed to tune its plasma effluent intensity in a low range to enhance the tissue (or cell) regeneration without damaging its viability.…”
Section: Discussionmentioning
confidence: 99%
“…This study evaluated the effects of LICAP on photoaginginduced wrinkles in an animal model and the expression profiles of extracellular matrix proteins in human dermal fibroblasts. LICAP was defined to distinguish the device from other conventional CAP devices that are designed to be used in a destructive manner, such as for skin resurfacing, [14][15][16] cancer therapy, 17 or tissue coagulation. 18 In this paper, the term LICAP indicates a physical plasma device that is designed to tune its plasma effluent intensity in a low range to enhance the tissue (or cell) regeneration without damaging its viability.…”
Section: Discussionmentioning
confidence: 99%
“…Standard facial images were captured using the VISIA-CR 2.3 system equipped with Mirror Photo Tools image management software 7.5.6 (Canfield Scientific, Inc., Parsippany, NJ, USA) [28]. Images of the right side of the face were taken following a consistent protocol.…”
Section: Eye Wrinklementioning
confidence: 99%
“… 14 A high-energy, double-pass multi-center study evaluating efficacy for wrinkle reduction and safety showed high patient satisfaction and marked improvement in Facial Wrinkle Scores (mean Independent Photographic Reviewer reduction of −3.6) along with mostly mild to moderate and mostly anticipated AEs that resolved in a reasonable time frame.15 Several hypertrophic scarring AEs were clustered at a single study site and were thought to be related to secondary wounding or to a variance in technique during energy delivery. 15 …”
mentioning
confidence: 99%